Cognitive-behavioral therapy for body dysmorphic disorder: A systematic review and meta-analysis of randomized controlled trials. (August 2016) - Harrison, Amy; Fernández de la Cruz, Lorena; Enander, Jesper; Radua, Joaquim; Mataix-Cols, David
Abstract: Body dysmorphic disorder (BDD) is a chronic and disabling psychiatric disorder unlikely to remit without treatment. A systematic review and meta-analysis of randomized controlled trials (RCTs) of cognitive-behavioral therapy (CBT) for BDD was conducted, including published and unpublished trials to 26th November 2015. Primary outcomes were validated BDD measures; secondary outcomes included depression and insight. Meta-regressions were conducted to examine potential effects of variables on the primary outcome, including socio-demographic variables, comorbidity, symptom severity/duration, concomitant medication, treatment duration, and methodological quality of the RCTs. Seven RCTs ( N = 299) met inclusion criteria. CBT was superior to waitlist or credible psychological placebo in reducing BDD (7 studies; delta = − 1.22, 95% CI = − 1.66 to − 0.79) and depression symptoms (5 studies; delta = − 0.49, 95% CI = − 0.76 to − 0.22). CBT was associated with improvements in insight/delusionality (4 studies; delta = − 0.56, 95% CI = − 0.93 to − 0.19). Improvement in BDD was maintained after 2–4 months follow-up (3 studies; delta = − 0.89, 95% CI = − 1.24 to − 0.54). Meta-regression analyses did not reveal any significant predictors of outcome. CBT is an efficacious treatment for BDD but there is substantial room for improvement. The specificity and long-term effects of CBT for BDD require further evaluation using credible control conditions. Additional trials comparing CBT with pharmacological therapies, as well as their combination, are warranted. Tele-care options, such as Internet-based CBT, hold great promise to increase access to evidence-based treatment for a majority of patients who need it and should be evaluated further. Highlights: CBT for BDD is efficacious and associated with large sized symptom improvement. Treatment gains are maintained 2–4 months after treatment. CBT for BDD improves accompanying features (depression and insight/delusionality). Internet-based CBT may help improve access to evidence-based treatments for BDD. Additional trials are required to test the specificity of CBT for BDD.